Status of Bird Conservation at the Ketambe Research Station, Gunung Leuser National Park - Masykur Masykur; Hartono Salim; Aida Fithri; Widya Sari (Postgraduate, University of Mataram, 2023)
The conservation status of birds in the Ketambe Research Station area, Gunung Leuser National Park, needs to be done so that more attention can be paid to the preservation of bird diversity. This study aims to observe the conservation status of various birds in three altitude zones, namely zone 1 (350-550 m asl), zone 2 (550-800 m asl), and zone 3 (800-1050 m asl). Observations were made in May-August 2019 at the Ketambe Research Station, Gunung Leuser National Park, Southeast Aceh. The results of observations as a whole, there were 581 individuals from 97 recorded bird species belonging to 27 families and 10 orders. Twenty-five bird species are listed on the IUCN red list in the categories of critically endangered, vulnerable, endangered and near threatened.